2009
DOI: 10.1371/journal.pone.0004983
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Stress Mediates the Honesty of Social Signals

Abstract: BackgroundExtravagant ornaments used as social signals evolved to advertise their bearers' quality. The Immunocompetence Handicap Hypothesis proposes that testosterone-dependent ornaments reliably signal health and parasite resistance; however, empirical studies have shown mixed support. Alternatively, immune function and parasite resistance may be indirectly or directly related to glucocorticoid stress hormones. We propose that an understanding of the interplay between the individual and its environment, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
97
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 45 publications
4
97
0
3
Order By: Relevance
“…An effect of parasitism on CORTf has been documented in previous studies (Bortolotti et al 2009b, Harriman et al 2014, indicating that this measure is sensitive enough to detect the effects of parasites. In socially monogamous red grouse, both sexes display conspicuous red combs and comb size functions in intra-and inter-sexual selection.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…An effect of parasitism on CORTf has been documented in previous studies (Bortolotti et al 2009b, Harriman et al 2014, indicating that this measure is sensitive enough to detect the effects of parasites. In socially monogamous red grouse, both sexes display conspicuous red combs and comb size functions in intra-and inter-sexual selection.…”
Section: Introductionmentioning
confidence: 69%
“…Numbers above error bars = sample sizes (number of females) 2014; Sild et al 2014) (although estimated parasite abundances may possibly have been too low to have had such an effect). Alternatively, higher corticosterone levels may have induced a greater susceptibility to infective larvae (Mougeot et al 2005b) and a greater reinfection rate, as also shown in male red grouse following a standardized challenge with infective larvae (Bortolotti et al 2009b). Previous experiments showed that parasite transmission likely occurs within red grouse social pairs (Martinez-Padilla et al 2012).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations